Analisis Pemanfaatan Pembelajaran Project Based Learning Berbasis Teknologi Digital Terhadap Gaya Belajar Peserta Didik VIII-B SMP IT Al Fateeh Semarang - Ermy Dara Yuspa; Aida Azizah (Perspektif Pendidikan dan Keguruan, 2025)
This study was conducted to improve students' motivation and understanding through the application of the Project Based Learning (PjBL) method in class VIII-B of SMP IT Al Fateeh. The research approach used in this study is a qualitative descriptive approach, with data sources derived from students' difficulties in understanding advertising texts, slogans, and posters during the learning process. These difficulties include a lack of understanding of the structure, meaning, and function of the three types of text. The results of this study indicate that the application of the Project Based Learning method can significantly improve students' understanding. This can be seen from the results of the assessment before using the PjBL method, which shows that students' learning achievements are still low. After this method was implemented, there was an increase in both assessment results and student and teacher activities. With a project-based approach, students become more active in exploring materials, collaborating, and developing critical and creative thinking skills.